2010
DOI: 10.3201/eid1607.091757
|View full text |Cite
|
Sign up to set email alerts
|

Dogs as Sentinels for Human Infection with Japanese Encephalitis Virus

Abstract: Because serosurveys of Japanese encephalitis virus (JEV) among wild animals and pigs may not accurately reflect risk for humans in urban/residential areas, we examined seroprevalence among dogs and cats. We found that JEV-infected mosquitoes have spread throughout Japan and that dogs, but not cats, might be good sentinels for monitoring JEV infection in urban/residential areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…The screening of hybridomas was performed by either PRNT or indirect immunofluorescence assay (IFA) using JEV/sw/Chiba/88/2002. PRNT was carried out as described previously [16,[19][20][21]. For IFA, fluorescein-conjugated goat anti-mouse IgM+IgG+IgA (Southern Biotech, Birmingham, AL, U.S.A.) was used as a secondary antibody.…”
Section: Japanese Encephalitis Virus (Jev) Is a Member Of Genusmentioning
confidence: 99%
“…The screening of hybridomas was performed by either PRNT or indirect immunofluorescence assay (IFA) using JEV/sw/Chiba/88/2002. PRNT was carried out as described previously [16,[19][20][21]. For IFA, fluorescein-conjugated goat anti-mouse IgM+IgG+IgA (Southern Biotech, Birmingham, AL, U.S.A.) was used as a secondary antibody.…”
Section: Japanese Encephalitis Virus (Jev) Is a Member Of Genusmentioning
confidence: 99%
“…We previously reported that 25% of dogs had virus-neutralizing (VN) antibodies against JEV, with particularly high seropositivities detected in the Kyushu (47%) and Shikoku (61%) districts of western Japan [11]. Despite the relative importance in sero-epidemiological studies, the duration of anti-JEV antibodies after JEV infection in dogs remains unknown.…”
mentioning
confidence: 99%
“…VN titers of JaOH0566 were measured as described previously [8,11]. The results showed that until day 21 postinfection in dogs No.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Titration was performed in a conventional plaque assay with Vero9013 cells [15,18]. RNA was extracted from virus-infected C6/ 36 cells using the RNeasy Mini Kit (Qiagen, Tokyo, Japan), reverse-transcribed by AMV reverse transcriptase with a random primer (Takara, Tokyo, Japan), and then used for polymerase chain reaction (PCR) with LA Taq DNA polymerase (Takara), and primer pairs reported by Yun et al [24].…”
mentioning
confidence: 99%